Implementing a virtual 3d campus of USM using second life: case for CCIL based distance learning package. - Jamaludin, Rozinah
The recent years have witnessed incredible technological developments. Educationalists have started to digest the revolution and radically rethinking the centuries old model of teaching and learning. Web 2.0 educational based methods is one of the novel areas of pedagogical research. The 3D virtual worlds represents one of the latest and highest potential Web 2.0 tools, in particular in the context of distance learning. The author envisage that the majority of learning activities will take place in distance within 1-2 decades.